1999
DOI: 10.1002/(sici)1099-1085(19991215)13:17<2675::aid-hyp841>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Variations in snowmelt energy and energy balance characteristics with larch forest density on Mt Iwate, Japan: observations and energy balance analyses

Abstract: Abstract:The variation in snowmelt energy and energy components were evaluated with respect to forest density. Surface snowmelt rates, surface evaporation from snow cover and meteorological elements were measured in the open and under sparse (411 trees/ha) and dense (1433 trees/ha) larch canopies. The surface snowmelt rate decreased as the forest density increased. Based on the observations and energy balance analyses, we concluded the following.(1) Albedo decreased while the bulk coecient for latent heat incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 16 publications
4
37
1
Order By: Relevance
“…It can be considered as a small-scale snowmelt lysimeter that works for short periods of time during which the device is not left unattended. This methodology has been commonly used in alpine environments (Kaser, 1982;Suzuki et al, 1999;Jackson and Prowse, 2009;Froyland, 2013) where rough meteorological conditions prevent the use of the more precise but delicate instrumentation. The main disadvantage of this method is that it provides us with discrete results that have to be obtained manually and, with respect to EC, that it needs some adequate measures or estimates of the parameters used for calculating the turbulent exchange of latent and sensible heat.…”
Section: Introductionmentioning
confidence: 99%
“…It can be considered as a small-scale snowmelt lysimeter that works for short periods of time during which the device is not left unattended. This methodology has been commonly used in alpine environments (Kaser, 1982;Suzuki et al, 1999;Jackson and Prowse, 2009;Froyland, 2013) where rough meteorological conditions prevent the use of the more precise but delicate instrumentation. The main disadvantage of this method is that it provides us with discrete results that have to be obtained manually and, with respect to EC, that it needs some adequate measures or estimates of the parameters used for calculating the turbulent exchange of latent and sensible heat.…”
Section: Introductionmentioning
confidence: 99%
“…For dry snow conditions at forest and open sites, snow albedo was assumed to be 0.8. Wet snow surface albedo values for open and forest sites during a thaw period were taken from our previous snowmelt research in northern Japan (Suzuki et al, 1999a) as 0.57 and 0.51, respectively. We assumed the roughness length over snow surfaces as constant.…”
Section: Description Of the Land Surface Modelmentioning
confidence: 99%
“…13(b)-(d) because snow surface temperature never exceeded 0 • C. This result was similar to that of Berris & Harr (1987), who reported large discharges in deforested watersheds in comparison to forested watersheds, due to larger turbulent fluxes. Suzuki et al (1999a) also reported that the sensible heat flux was the dominant energy balance component causing differences in snowmelt energy due to forest density.…”
Section: Snowmeltmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of needles, leaves, bark, and other debris on sub-canopy snow can reduce the albedo (Link and Marks 1999). Turbulent fluxes and short wave radiation are lower and longwave radiation is greater in the forest compared to open areas and these effects increase with forest density (Suzuki et al 1999). The lower energy inputs to the snow surface can sometimes be offset by the increased longwave radiation from the canopy (Hardy et al 1997;Pomeroy et al 2009).…”
Section: Energy Budget In Mountainous Terrainmentioning
confidence: 99%